ANALISIS PSIKOLOGI DAN NILAI PENDIDIKAN KARAKTER DALAM NOVEL MATA DI TANAH MELUS SERTA PEMANFATAANNYA DALAM PEMBELAJARAN SASTRA - Kinanti, Ainidya Marhaenita; Andayani, Andayani; Suyitno, Suyitno (Universitas Sebelas Maret, 2020)
The objectives of this research are to describe and explain (1) the structure of novel Mata di Tanah Melus by Okky Madasari; (2) the psychological aspects of main character in the novel based on human needs’ theory by Abraham Maslow; (3) the value of education character in the novel Mata di Tanah Melus; (4) to describe relevance in the novel with literature learning in the junior high school. This research used a qualitative descriptive method in psychology literature to describe psychological aspects of the main character. The data source of this research is the novel entitled Mata di Tanah Melus by Okky Madasari publised Gramedia Pustaka Utama. The validaty data used the triangulation data source. The results show that (1) the novel structures are theme, character and characterization, plot, and setting; (2) the psychplogical aspect of main character based of human needs’ theory are included; a physiological needs, the needs of savety, love and belonging, esteem of Matara are not fulfill well; (3) the most dominant value of caracter education is curiosity; (4) the relevance of the novel with literature learning in the junior high school based on the results of interviews.